The Implementation of KWL Teaching Technique to Improve Students’ Reading Achievement of The Third Graders of Masa Depan Cerah Elementary School - Theresia Ayu Kusdwiharini (Widya Mandala Surabaya Catholic University, 2014)
Understanding a text employs the high level of reading comprehension technique. The reading achievement score of Masa Depan Cerah (MDC) elementary school students, especially those of the third graders were quite low, that is 65 (the average score), which is below the minimum passing mark (70). Among the problems that occur in the third graders’ reading class, the innapropriate teaching teachnique was the main cause. To overcome the low reading achievement for the third graders of Masa Depan Cerah (MDC) elementary school, KWL (Know, Want and Learn) technique was selected to be applied to the teaching of reading. KWL helps the students to activate their schemata to comprehend the text enjoyably. Since it provides the students opportunity to comprehend the text through class discussion, games, pictures identification etc.. By doing so, the students would increase their reading comprehension achievement score. Nevertheless, the teaching reading is successfully done through the implementation of KWL